Two co-inherited SNPs of the telomerase reverse transcriptase (TERT) gene are associated with Iraqi patients with lung cancer - Lawi Zahraa K.; Alkhammas Ahmed H.; Elerouri Malek; Ben Amara Ibtissem; Al-Shuhaib Mohammed Baqur S. (Journal of Medical Biochemistry, 2023)
Background: The telomerase reverse transcriptase (TERT) gene is essential polymorphic loci linked to most malignant tumors. This study assessed the association between the TERT gene and non-small cell lung carcinoma (NSCLC) in Iraq. Methods: Genomic DNA samples were extracted from a total of 200 samples of blood. Four specific PCR fragments were designed to amplify four high-frequency rs2735940, rs2736098, rs2736100, and rs10069690 SNPs within the TERT gene. Single-strand conformation polymorphism (SSCP) followed by sequencing reactions were used for genotyping and validating the amplified fragments. Results: Individuals with the genotype rs2735940: A/G were at a significantly greater risk of developing NSCLC (P=0.0299; OD 2.3158; Cl95% 1.0853 to 4.9414). Individuals with the genotype rs2736098: C/T were also significantly associated with the increased likelihood of developing NSCLC (P=0.0363; OD 2.1583; Cl95% 1.0503 to 4.4351). Linkage disequilibrium analysis showed that both SNPs showed a very high level of patient coinheritance. The LD plot showed that allele T of rs2736098 had collaborated with allele G of rs2735940 to generate TG haplotype in patients. According to our findings, both TERTrs2735940: A/G and TERT-rs2736098: C/T SNPs were found to be significant associations with the elevated risk of NSCLC. Both SNPs showed the highest values of co-inheritance in patients. This co-inheritance is mainly represented by alleles rs2735940: A and rs2736098: C. Both pathogenic T and G alleles have generated TG haplotype that is only available in patients' samples. Conclusion: This study suggests employing the haplotype TG as a promising biomarker for the early diagnosis of NSCLC. These findings need further validation by largescale investigation with a larger size of samples in the study population.